Professional identity of college counselors in Shandong - Qiang, Gao (Panpacific University : [s.n.], 2020)
College counselors shoulder the important task of ideological and political education for college students and guiding their growth. This study, through an analysis of the existing literature, a questionnaire-based survey, statistical analysis and a combination of various other methods, objectively reflect the Shandong College counselors professional identity status and influencing factors. It is expected to provide theoretical reference and guidance for the professional development of college counselors in Shandong and promote the construction and development of college counselors within the province. The results indicated that college counselors in Shandong, China experienced a moderate level of professional identity and there were no significant differences among these levels by the sex, age, marital status, major and professional title of the college counselors. With regard to the factors influencing professional identify, there was found a significant difference in terms of professional behavior between male and female. In terms of age, a significant difference in the impact of influencing factors was found between those under 25 years and those aged 31-35 along the lines of professional volition and professional behavior. In terms of number of years of work, significant differences in professional volition were found between those with 0-2 years experience and those with 6-8 years of experience. Also, in terms of the highest educational attainment, significant difference were discovered between those with junior college diplomas and those with bachelor's and master's degree. The professional identity of college counselors was found to be influenced by social, organizational, and personal factors. With these, an action plan to improve the professional identity of college counselors was proposed and shall be implemented.
References: pages 111-126.
CHED-La Union
Keywords: Colleges and universities -- Counselors